PENGARUH MATA KULIAH MICRO TEACHING TERHADAP KEMAMPUAN PEDAGOGIK MAHASISWA FAKULTAS TARBIYAH ANGKATAN 2018 DI INSTITUT AGAMA ISLAM (IAI)AL-AZHAAR KOTA LUBUKLINGGAU - Reni Marlena; Nurus Amzana; Sopatun Nahwiyah; Lia Luvita; Muhamad Basyir (PAI RAFAH, 2023)
This research is motivated by the discovery of several students who failed when carrying out teaching practices in micro teaching courses even though it can be seen that more or less students of the Faculty of Tarbiyah, Islamic Religious Institute (IAI) Al-Azhaar Lubuklinggau have experience in teaching. The results of this study can be concluded that a) Micro teaching courses have an influence on the pedagogical abilities of Faculty of Tarbiyah Students Class of 2018 at the Institute of Islamic Religion (IAI) Al-Azhaar Lubuklinggau City. b) Micro teaching courses have a strong or high influence on the pedagogical abilities of students of the Faculty of Tarbiyah Class of 2018 at the Institute of Islamic Religion (IAI) Al-Azhaar Lubuklinggau City. This is evident from the results of the calculation of the correlation coefficient interpretation analysis which obtained a score of 0.61, and after being consulted with the "r" table 0.61 is in the interval class between 0.61-0.80, meaning that between the micro teaching course and the pedagogical abilities of the 2018 Faculty of Tarbiyah students have a high or strong relationship so that the correlation can be accepted. Therefore, the Ha hypothesis can be accepted because it can be proven true, while Ho is not accepted because it is not proven true.